KONSEP MASHLAHAH PERSPEKTIF MUHAMMAD SA’ÎD RAMADHÂN AL-BÛTHÎ - Maimun Nawawi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2010)
Mashlahah is often made identically with benefit. It hasplaced in one of fields in Islamic law study, especially inushûl al-fiqh. It has a role in determining a debatable lawconclusion. It is also as essence of maqâshid al-syarî’ah thatis needed in every law consideration. The problem ishow to determine a law illah that has mashlahah, and whohas a role in determining and assessing mashlahah, onlyGod (syari’) or mukallafkah, if mukallaf has a right, how farit has its power to determine a mashlahah in certain lawcontext. This writing will give its description.